2006
DOI: 10.4049/jimmunol.176.12.7171
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Control Uveoretinitis Induced by Pathogenic Th1 Cells Reacting to a Specific Retinal Neoantigen

Abstract: In many clinical cases, uveitis develops secondary to an infection. This could result from peripheral activation followed by ocular penetration and reactivation of T cells specific for microbial Ags expressed in the retina. To gain insights into the pathophysiology of uveitis, we developed a new mouse model based on stable retinal expression of influenza virus hemagglutinin (HA) neoantigen by adeno-associated virus-mediated gene transfer. One month thereafter, we adoptively transferred HA-specific T cells, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 52 publications
1
13
0
1
Order By: Relevance
“…21 We studied 3 different conditions of adoptive transfer in BALB/c mice in the presence or absence of IVIg infusion: CFSE-labeled HA-specific CD4 ϩ CD25 Ϫ Tconv alone, CD4 ϩ CD25 ϩ T cells alone (Treg), and a mixture of CD4 ϩ CD25 Ϫ T cells (90%) with CD4 ϩ CD25 ϩ T cells (10%; Tconv ϩ Treg). Cell transfer was followed by immunization with HA 126-138 peptide in CFA.…”
Section: Mechanisms Underlying the Ivig-mediated Expansion Of Tregmentioning
confidence: 99%
“…21 We studied 3 different conditions of adoptive transfer in BALB/c mice in the presence or absence of IVIg infusion: CFSE-labeled HA-specific CD4 ϩ CD25 Ϫ Tconv alone, CD4 ϩ CD25 ϩ T cells alone (Treg), and a mixture of CD4 ϩ CD25 Ϫ T cells (90%) with CD4 ϩ CD25 ϩ T cells (10%; Tconv ϩ Treg). Cell transfer was followed by immunization with HA 126-138 peptide in CFA.…”
Section: Mechanisms Underlying the Ivig-mediated Expansion Of Tregmentioning
confidence: 99%
“…In this model, we previously showed that i.v. injection of HA-specific Treg (HA-Treg) cells controlled uveitis (13). In this study, we analyzed the therapeutic efficacy of these HA-Treg cells after in situ injection (2 3 10 5 cells injected in the vitreous) versus systemic injection (2 3 10 6 cells injected in the blood).…”
Section: Therapeutic Effect Of Intravitreous Injection Of Treg Cells mentioning
confidence: 99%
“…We assessed the therapeutic potential of Treg cells in uveitis in a mouse model that we have described previously (13). Briefly, the disease was induced by transferring effector T (Teff) cells specific for the HA model Ag (HA-Teff cells) into mice that stably expressed HA in the retina.…”
Section: Therapeutic Effect Of Intravitreous Injection Of Treg Cells mentioning
confidence: 99%
See 1 more Smart Citation
“…Another example was experimental uveitis in mice. Terrada et al 75 showed that Treg depletion exacerbates uveitis whereas Treg injection controls it. Tregs are also particularly important in chronic infections such as leishmanosis and malaria and are also involved in inhibiting immune responses against cancer.…”
mentioning
confidence: 99%